2018
DOI: 10.1002/ccd.28014
|View full text |Cite
|
Sign up to set email alerts
|

Incremental cost and length of stay associated with postprocedure delirium in transcatheter and surgical aortic valve replacement patients in the United States

Abstract: Objectives: To explore the impact of post-procedure delirium on resource utilization following transcatheter and surgical aortic valve replacement (TAVR and SAVR, respectively).Background: Postprocedure delirium is associated with worse long-term survival after TAVR and SAVR. However, its effect on resource utilization has been understudied.Methods: Using the 2015 Medicare Provider Analysis and Review File (MedPAR), we retrospectively analyzed elderly (≥80 years) Medicare beneficiaries receiving either SAVR or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…Prior research has shown conflicting results with regard to the association of PNDs with an increased length of inpatient hospitalizations. [23][24][25] In this study, presence of a PND was associated with a more than 1-day increase in the mean length of stay. Although it is possible that the length of stay was associated with the increased costs for the acute in-hospital payments for the index hospitalization that was observed, it is noteworthy that the difference, albeit statistically significant,…”
Section: Discussionmentioning
confidence: 50%
“…Prior research has shown conflicting results with regard to the association of PNDs with an increased length of inpatient hospitalizations. [23][24][25] In this study, presence of a PND was associated with a more than 1-day increase in the mean length of stay. Although it is possible that the length of stay was associated with the increased costs for the acute in-hospital payments for the index hospitalization that was observed, it is noteworthy that the difference, albeit statistically significant,…”
Section: Discussionmentioning
confidence: 50%
“…Previous studies have evaluated the effect of delirium on health care resources utilization among patients with TAVR, but not other geriatric syndromes (frailty and dementia or combinations of those three geriatric syndromes). 9,10 Our results showed that geriatric syndromes, especially delirium, play a substantial role in increasing health care expenditure for patients with TAVR.…”
Section: Figure 3 Predicted Average Los For Each Condition From the mentioning
confidence: 71%
“…Our findings are consistent with the results of previous studies, showing that delirium or frailty increases the hospital cost or LOS. 9,10,27 While frailty is a rather underlying condition, delirium develops during the hospitalization; considering that it poses the most substantial impact, it resonates with the importance of the effort to prevent delirium among patients who are undergoing TAVR.…”
Section: Figure 2 Predicted Average Total Hospital Cost Of Each Condmentioning
confidence: 99%
See 1 more Smart Citation
“…Examining Medicare patients over the age of 80, transcatheter aortic valve replacement (TAVR) was less likely to generate a billing code for delirium (1.6%) than surgical aortic valve replacement (SAVR) at 3.6% ( p < .0001) in Potter's study . This occurred despite the TAVR patients being older with greater comorbidities, perhaps heralding another improvement in outcome with TAVR compared to SAVR.…”
mentioning
confidence: 97%